TRAINING OF PERFORMING ARTS MANAGEMENT SKILLS IN THE ART CULTURE COMMUNITY: TRAINING OF PERFORMING ARTS MANAGEMENT SKILLS IN THE ART CULTURE COMMUNITY - Jimy O. Andin; Elvira (Tambur : Journal of Music Creation, Study and Performance, 2022)
Art management related to coordination, in a performance planning, publication, promotion, audience and financial/funding and other general matters is very important for an organization/community/art culture studio. All non-artistic work is under the responsibility of Production, including training schedules and staging dates. The purpose of this training is to provide training to every cultural arts community in the city of Palangkaraya and the Watershed Cultural Community (Daerah Aliran Sungai). Participants who received field practice training, both training on stage managers (production teams) for performances and management in arts and culture community organizations so that an orderliness of personal affairs was achieved on every problem in the cultural community concerned. The method used in this training is carried out online because the Covid-19 pandemic is still ongoing and still increasing, following the rules of the Covid-19 handling/prevention officer unit at the local government level and the University of Palangkaraya, this activity was decided to be an online activity using the Zoom Meeting application which attended by 180 participants from various circles, both students, art lecturers and art activists.